2016
DOI: 10.1016/j.jacc.2015.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Strategies for the Evaluation of Chest Pain

Abstract: SCOT-HEART and PROMISE represent the 2 largest and most comprehensive cardiovascular imaging outcome trials in patients with stable chest pain, and provide significant insights into patient diagnosis, management, and outcomes. These trials are particularly timely, given the well-recognized knowledge gaps and widespread use of noninvasive imaging. The overall goal of this review is to distill the data generated from these 2 pivotal trials to better inform the practicing clinician in the selection of noninvasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 43 publications
1
21
1
Order By: Relevance
“…In order to understand the reasons for risk estimate imprecision we need to consider carefully the differences in patient populations between the PROMISE and SCOT-HEART trials. Such differences have previously been reported [16] , but specific areas of relevance to the current findings warrant mention. First, the improvement in discrimination seen with the SCOT-HEART population is likely to reflect the greater breadth of baseline risk which gives rise to a broader spread of the linear predictors within the validation cohort [17] .…”
Section: Discussionsupporting
confidence: 75%
“…In order to understand the reasons for risk estimate imprecision we need to consider carefully the differences in patient populations between the PROMISE and SCOT-HEART trials. Such differences have previously been reported [16] , but specific areas of relevance to the current findings warrant mention. First, the improvement in discrimination seen with the SCOT-HEART population is likely to reflect the greater breadth of baseline risk which gives rise to a broader spread of the linear predictors within the validation cohort [17] .…”
Section: Discussionsupporting
confidence: 75%
“…This may account for why individuals presenting with chest pain classified as nonanginal comprised merely 11% within PROMISE compared with 41% in SCOT-HEART. In contrast, only 72% of patients within PROMISE described chest pain as the primary symptom compared with the entire SCOT-HEART cohort (10) , perhaps explaining the 2-fold greater prevalence of obstructive CAD in the latter, despite comprising a population at apparently lower cardiovascular risk, as determined by the Framingham score.…”
Section: Discussionmentioning
confidence: 95%
“…The intervention arm in both studies consisted of CCTA, which was compared with usual care. Details of cohort-specific inclusion and exclusion criteria have been previously described (10) . To confirm guideline utility in distinct clinical settings and across populations, the study cohorts were analyzed separately.…”
Section: Methodsmentioning
confidence: 99%
“…Coronary computed tomography angiography is now considered a reasonable or preferred first line investigation for patients with suspected CAD, 12–14 as studies have suggested improved clinical outcomes for patients managed based on initial CCTA rather than alternative non-invasive tests. 4 While, CCTA has been proven to be an effective diagnostic tool, there remain concerns regarding fairly high rates of downstream ICA and resource utilization as well as the lack of physiological information available to guide treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%